Mnemonic Solidarity Global Interventions - Lim, Jie-Hyun; Rosenhaft, Eve (Entangled Memories in the Global South,, 2021)
This open access book provides a concise introduction to a critical development in memory studies. A global memory formation has emerged since the 1990s, in which memories of traumatic histories in different parts of the world, often articulated in the terms established by Holocaust memory, have become entangled, reconciled, contested, conflicted and negotiated across borders. As historical actors and events across time and space become connected in new ways, new grounds for contest and competition arise; claims to the past that appeared de-territorialized in the global memory formation become re-territorialized - deployed in the service of nationalist projects. This poses challenges to scholarship but also to practice: How can we ensure that shared or comparable memories of past injustice continue to be grounds for solidarity between different memory communities? In chapters focusing on Europe, East Asia and Africa, five scholars respond to these challenges from a range of disciplinary perspectives in the humanities. .